2012
DOI: 10.3233/wor-2012-0917-5677
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between heart rate as an indicator of work hardness and results of dynamometry

Abstract: Heart rate is associated with work hardness and increase linearly with its increasing. In the average of energy consumption, heart rate measurement is simple but non-accurate method for calculation of work hardness. Our purpose in this research was to evaluate the relationship between heart rate and dynamometry results with hypothesis of work hardness effectiveness on the human power. This study was conducted on 102 porcelain workers. Participants were selected randomly. The research tools include stethoscope,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Together with its simplicity and portability, this -up till now seldom-used -apparatus might be an appropriate tool in research lab, field research, and clinical settings. Currently, the usefulness of the BLC dynamometer has been described rarely (Coleman et al, 2011;Sadeghi et al, 2012;Sener et al, 2013). Coleman and colleagues (2011) used the BLC dynamometer in patients with Multiple Myeloma, and showed that fatigue, pain, sleep, mood and functional performance were interrelated.…”
Section: Discussionmentioning
confidence: 99%
“…Together with its simplicity and portability, this -up till now seldom-used -apparatus might be an appropriate tool in research lab, field research, and clinical settings. Currently, the usefulness of the BLC dynamometer has been described rarely (Coleman et al, 2011;Sadeghi et al, 2012;Sener et al, 2013). Coleman and colleagues (2011) used the BLC dynamometer in patients with Multiple Myeloma, and showed that fatigue, pain, sleep, mood and functional performance were interrelated.…”
Section: Discussionmentioning
confidence: 99%